Resistance to the Plant Defensin NaD1 Features Modifications to the Cell Wall and Osmo-Regulation Pathways of Yeast - McColl, Amanda I.; Bleackley, Mark R.; Anderson, Marilyn A.; Lowe, Rohan G. T. (Frontiers in Microbiology, 2018)
Over the last few decades, the emergence of resistance to commonly used antifungal molecules has become a major barrier to effective treatment of recurrent life-threatening fungal diseases. Resistance combined with the increased incidence of fungal diseases has created the need for new antifungals, such as the plant defensin NaD1, with different mechanisms of action to broaden treatment options. Antimicrobial peptides produced in plants and animals are promising new molecules in the arsenal of antifungal agents because they have different mechanisms of action to current antifungals and are often targeted specifically to fungal pathogens (van der Weerden, et al. 2013). A key step in the development of novel antifungals is an understanding of the potential for the fungus to develop resistance. Here we have used the prototypic plant defensin NaD1 in serial passages with the model fungus S. cerevisiae to examine the evolution of resistance to plant antifungal peptides. The yeast strains did develop tolerance to NaD1, but it occurred more slowly than to the clinically used antifungal caspofungin. Sequencing the genomes of the strains with increased tolerance failed to identify any ‘hotspot’ mutations associated with increased tolerance to NaD1 and led to the identification of 12 genes that are involved in resistance. Characterization of the strains with increased tolerance to NaD1 also revealed changes in tolerance to abiotic stressors. Resistance developed slowly via an accumulation of single nucleotide mutations and had a fitness penalty associated with it. One of the genes identified FPS1, revealed that there is a common mechanism of resistance to NaD1 that involves the osmotic stress response pathway. These data indicate that it is more difficult to generate resistance to antimicrobial peptides such as NaD1 compared to small molecule antifungals.